Malaysia small medium enterprises (SMES) strategic orientation and access to financial technology (fintech) financing moderate by entrepreneur innovativeness - Chooi, Wei San (2023)
With the advent of Fintech financing, innovativeness plays a significant role in enhancing SMEs’ access to financing. Three comprehensive constructs, namely, market, learning and technology orientation, are adopted to present a holistic picture of the effect of strategic orientation on Malaysian SMEs’ access to Fintech financing, moderated by entrepreneur innovativeness. This study adopted a survey research design based on 213 Malaysian SMEs and analysed the data using the PLS-SEM software. The results indicated that strategic orientation (market, learning and technology) influences SMEs’ access to Fintech financing. However, the moderating impact of entrepreneur innovativeness is insignificant in the relationship between strategic orientation and access to Fintech financing. Technological innovation is reshaping commerce and the economy across all sectors. SMEs need to access external sources of information, knowledge, expertise and technology in order to build their own innovative capability for accessing finance and reach their markets over the long run. The study contributes to the policymakers obtaining a better understanding of the aspect of strategic orientation for SMEs’ access to Fintech financing and provides assistance to the SMEs. This study also contributes to regulators in developing relevant policies or frameworks.